Climate Elasticity of Low Flows in the Maritime Western U.S. Mountains. Issue 8 (19th August 2018) - Cooper, M. G.; Schaperow, J. R.; Cooley, S. W.; Alam, S.; Smith, L. C.; Lettenmaier, D. P.
Abstract: Summer streamflow is an important water resource during the dry summers in the western United States, but the sensitivity of summer minimum streamflow (low flow) to antecedent winter precipitation as compared with summer evaporative demand has not been quantified for the region. We estimate climatic elasticity of low flow (percent change in low flow divided by percent change in climatic forcing variable) with respect to annual maximum snow water equivalent ( E SWE ), winter precipitation ( E PPT ), and summer potential evapotranspiration ( E PET ) for 110 unmanaged headwater catchments in the maritime western U.S. mountains. We find that | E PET | is larger than | E PPT | and | E SWE | in every catchment studied and is 4–5 times larger than both, on average. Spatial variations in E are dominated by three patterns. First, | E PPT |, | E SWE |, and | E PET | are largest and most variable among semiarid catchments and decrease nonlinearly with increasing values of the humidity index (the ratio of annual precipitation to annual evaporative demand). Second, | E PPT | and | E PET | are lower in snow‐dominated catchments than in rain‐dominated catchments, suggesting that snow cover reduces the proportional response of low flows to climatic variability. Third, | E PPT |, | E SWE |, and | E PET | are lower in slow‐draining catchments than in fast‐draining catchments, for which baseflow recession storage coefficients are used to represent the rate at which catchment water storage is translated into streamflow. Our results provide the first comparison of summer low‐flow elasticity to PPT versus PET and its spatial variation in the maritime western U.S. mountains. Plain Language Summary: The western U.S. climate is characterized by cool, wet winters and warm, dry summers. Streamflow provides a critical water resource during the dry summers here. The minimum streamflow (low flow) usually occurs in September or October, several months after the mountain snowpack has melted. The magnitude of the low flow sets a lower bound on water supply, especially in systems without surface water storage. However, it is not clear whether the magnitude of the low flow is more strongly controlled by how cold and wet the previous winter was versus how warm and dry the summer was. We quantified the percent change in low flows per 1% change in winter precipitation and summer evaporative demand. We found that percent changes in low flows are 4 to 5 times larger per 1% change in summer evaporative demand than winter precipitation. However, year‐to‐year variation in evaporative demand is small so the year‐to‐year variation in low flows is more strongly associated with year‐to‐year variation in winter precipitation. Our results suggest that low flows are highly vulnerable to small changes in evaporative demand, but more work is needed to understand expected changes in evaporation in a warming climate. Key Points: Summer low‐flow elasticity to evaporative demand is larger than elasticity to winter precipitation in every catchment studied in the maritime western United States Summer low‐flow elasticity to evaporative demand and winter precipitation is smaller in snow‐dominated catchments, on average Summer low‐flow elasticity to evaporative demand and winter precipitation is smaller in slow‐draining catchments, on average